Stored Grain Pests and Their Management - Khare, B.P; Khare, B.P (Ludhiana Kalayani)
This book described that the population of many countries is increasing fast and that will continue to increase for some decades more. it has been ecognised that in addition to stsbilizing population, & food production
Aspergillus Penicillium Rice Weevil
Keywords: Aspergillus, Penicillium ,Rice Weevil